The Future of Computer Science Profession (International Journal of Scientific Research and Management (IJSRM), 2022)
As society becomes more reliant on computers and the Internet, A computer science degree is a great way to start a career in IT. You can find many different roles that suit your interests and strengths. The best thing about computer science is that it teaches you to think logically and solve problems. Computer hardware and software technology quickly expand in power and complexity as this process unfolds. Because developments happen so quickly, predicting where the area of computer science will go in the next 10 to 20 years can be challenging. The area of computer science is expected to undergo significant changes shortly.